Analisis Perbandingan Metode Simple Additive Weighting (SAW) dan Weighted Product (WP) dengan Pembobotan Rank Order Centroid (ROC) dalam Pemilihan Mahasiswa Terbaik - Denissa A. Putri; Amelia H Ikhlas; Agus Iskandar (STMIK Budi Darma, 2023)
Students are the main element of a college. So that the assessment of the quality of a tertiary institution can be seen from the achievement and quality weight scores of each student studying at that tertiary institution. The university's awareness of this reality ultimately gave rise to the university's intention to increase student learning motivation. There are many ways in which universities can increase student motivation to become intellectual and qualified individuals. One way to motivate students is by giving awards to outstanding students. The problem is that there are so many students in higher education that it will be difficult to choose students of quality. To solve this problem, SPK is needed. SPK functions to help parties who are having difficulty making a decision. SPK requires a method. The methods used in this research are the SAW and WP methods with ROC weighting. The results obtained in this research are the first method SAW with a value of 0.9847 as the best alternative with code A7 in the name of Sapadi Sinebang. Compared with the WP method with a result of 0.1826 as the alternative with the highest value in the name of Sapadi Sinebang as the best alternative